Pricing strategies of tour operator and online travel agency based on cooperation to achieve O2O model. (October 2017) - Long, Yong; Shi, Pingping
Abstract: This paper studies the optimal pricing strategies of a tour operator (TO) and an online travel agency (OTA) when they achieve the O2O model through online sale and offline service cooperation. By constructing a competition model, cooperation conditions, pricing strategies and revenues are analyzed and compared in the Stackelberg and Bertrand game. Results indicate that service level, unit sale commission, service cost coefficient and unit service compensation coefficient have different influences on the TO's and OTA's pricing decisions. When the unit sale commission is greater than the threshold, the TO's and OTA's pricing in the Bertrand game are higher than in the Stackelberg game. Being a leader is the dominant strategy for the TO. In addition, the revenues of TO and OTA in sale and service cooperation are analyzed by numerical examples and some suggestions for establishing cooperation contract are provided. Highlights: Study the pricing games based on cooperation between the TO and OTA to achieve O2O model. Find the optimal pricing policy for the TO and OTA to maximize the revenue. Compare the optimal pricings and revenues in the Stackelberg and Bertrand game. Give suggestions to TOs and OTAs on how to cooperate.